Water Storage for Food Security in Nepal - Sharma, Khem Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Increasing trend of water scarcity for drinking, irrigation, hydropower generation and other purposes has been a serious challenge for Nepal. As food need rises, the country's reliance on irrigated agriculture increases. The existing run-of-river types of irrigation systems provide little leverage in providing adequate, timely and equitable water supply to the farmers' fields. With the approval of the 2002 Water Resources Strategy, the country is in the process of changing its water development paradigm from sect oral to integrated water resource management. In this context, intensification of agriculture is the most viable option of achieving food security and this requires assured supply of irrigation water which is possible mainly through water storage systems. Key words: Integrated Water Resources Management (IWRM); Irrigation; Water storage; Agriculture intensification; Nepal DOI: 10.3126/hn.v7i0.4234 Hydro Nepal Journal of Water, Energy and Environment Vol 7, July, 2010 Page: 35-37 Uploaded date: 31 January, 2011